Targeted multidomain intervention for complex mTBI: protocol for a multisite randomized controlled trial in military-age civilians - Elbin, R. J.; Trbovich, Alicia; Womble, Melissa N.; Mucha, Anne; Fedor, Sheri; Stephenson, Katie; Holland, Cyndi; Dollar, Christina; Sparto, Patrick; Durfee, Kori; Patterson, Charity G.; Smith, Clair N.; et al. (Frontiers in Neurology, 2023)
Background Mild traumatic brain injury (mTBI) affects 18,000 military personnel each year, and although most will recover in 3–4 weeks, many experience persisting symptoms and impairment lasting months or longer. Current standard of care for U.S. military personnel with complex mTBI involves initial (<48 h) prescribed rest, followed by behavioral (e.g., physical activity, sleep regulation, stress reduction, hydration, nutrition), and symptom-guided management. There is growing agreement that mTBI involves different clinical profiles or subtypes that require a comprehensive multidomain evaluation and adjudication process, as well as a targeted approach to treatment. However, there is a lack of research examining the effectiveness of this approach to assessing and treating mTBI. This multisite randomized controlled trial (RCT) will determine the effectiveness of a targeted multidomain (T-MD) intervention (anxiety/mood, cognitive, migraine, ocular, vestibular; and sleep, autonomic) compared to usual care (behavioral management) in military-aged civilians with complex mTBI. Methods This study employs a single-blinded, two-group repeated measures design. The RCT will enroll up to 250 military-aged civilians (18-49 yrs) with a diagnosed complex mTBI within 8 days to 6 months of injury from two concussion specialty clinics. The two study arms are a T-MD intervention and a usual care, behavioral management control group. All participants will complete a comprehensive, multidomain clinical evaluation at their first clinical visit. Information gathered from this evaluation will be used to adjudicate mTBI clinical profiles. Participants will then be randomized to either the 4-week T-MD or control arm. The T-MD group will receive targeted interventions that correspond to the patient’s clinical profile (s) and the control group will receive behavioral management strategies. Primary outcomes for this study are changes from enrollment to post-intervention on the Neurobehavioral Symptom Inventory (NSI), Patient Global Impression of Change (PGIC), and functional near-infrared spectroscopy (fNIRS). Time to return to activity (RTA), and healthcare utilization costs will also be assessed. Discussion Study findings may inform a more effective approach to treat complex mTBI in military personnel and civilians, reduce morbidity, and accelerate safe return-to-duty/activity. Ethics and dissemination The study is approved by the University of Pittsburgh Institutional Review board and registered at clinicaltrials.gov. Dissemination plans include peer-reviewed publications and presentations at professional meetings. Clinical Trial Registration: www.clinicaltrials.gov, identifier: NCT04549532.